The eurosystem money market auctions: A banking perspective - Craig, Ben; Fecht, Falko (Journal of Banking & Finance, 2007)
This paper analyzes the individual bidding behavior of German banks in the money market auctions conducted by the ECB from the beginning of 2000:IIIQ to the end of 2001:IQ. Our approach takes a variety of characteristics of the individual banks into account, particularly variables that capture the different use of liquidity and the different attitude towards liquidity risk of the individual banks. It turns out that these characteristics are reflected in banks’ bidding behavior. Thus, our study contributes to a deeper understanding of the way liquidity risk is managed in the banking sector.